Social Media Marketing Strategy to Increase Brand Loyalty in The Beef Trade: A Sharia Marketing Perspective - Wachidah, Siti Faridatul; Munawaroh, Nuril Aulia (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2025)
. Social media marketing plays an important role in building brand loyalty, especially in the beef trade sector, which can be seen through the perspective of sharia marketing. This study aims to analyze how social media marketing strategies that are in accordance with sharia principles can increase customer loyalty to brands. Using a qualitative approach, data was collected through in-depth interviews, observations, and document studies of beef businesses that apply sharia principles in marketing strategies. The results showed that transparency, honesty, and fairness in marketing communications is apply in Sharia values that can create customer trust. Social media activities such as sharing educational content, customer testimonials, and responsive interactions also help build of emotional relationships with the customers. By prioritizing ethics and Shariah values, social media marketing is not only a promotional tool but also strengthens customer loyalty to the brand in the long term